Outliers the story of success - Gladwell, Malcolm (New York Little Brown, 2008)
n this stunning new book, Malcolm Gladwell takes us on an intellectual journey through the world of "outliers"--the best and the brightest, the most famous and the most successful. He asks the question: what makes high-achievers different?
Keywords: Successful people